Analisis Pengaruh Edukasi Melalui Media Video terhadap Tingkat Pengetahuan Pasien Diabetes Melitus Tentang Perawatan Kaki di Puskesmas: Analysis of The Influence of Education Through Video Media on The Level of Knowledge of Diabetes Mellitus Patients About Foot Care at Puskesmas - Almira Sekar Octaviana; Anita Kumala Hati (Indonesian Journal of Pharmacy and Natural Product, 2023)
Video media is effectively used as an effort to increase one's knowledge of information, media can show images that can move and have sound. The purpose of this study was to analyze the effectiveness of education about foot care using video on the level of knowledge of DM patients. This study used quasy-experimental design, pretest and posttest with control group, as many as 30 samples at Bawen Health Center and 30 samples at Suruh Health Center, which were taken by total sampling technique. Data were analyzed with the Wilcoxon test and Mann-Whitney with a 95% confidence level. The results of this study showed that most DM patients aged 56-65 years, with 12 men and 48 women. The results of the Wilcoxon test before and after in the treatment group were 0,000 which means that there was a significant difference after being given educational videos, and for the control group was 1,000 which means there was no significant difference. The results of the Mann-Whitney test before being given an educational video was 0.957 which means that there was no significant difference between the treatment and control groups, while after being given an educational video was 0.000 which means that there was a significant difference between the treatment and control groups. Providing education with video had been significantly increased foot care knowledge in type 2 DM patients. ABSTRAK Media video dapat membantu meningkatkan pengetahuan seseorang tentang informasi karena memiliki gambar bergerak dan suara. Tujuan penelitian ini yaitu untuk menganalisis efektivitas edukasi tentang perawatan kaki terhadap tingkat pengetahuan pasien DM. Penelitian ini menggunakan quasy-experimental design, pretest and posttest with control group, sebanyak 30 sampel di Puskesmas Bawen dan 30 sampel di Puskesmas Suruh, yang diambil dengan teknik total sampling. Data dianalisis dengan uji Wilcoxon dan Mann-Whitney dengan taraf kepercayaan 95%. Hasil penelitian ini menunjukkan pasien DM paling banyak usia 56-65 tahun, dengan jenis kelamin laki-laki 12 orang dan perempuan 48 orang. Hasil Uji Wilcoxon sebelum dan sesudah pada kelompok perlakuan didapatkan (0.000) artinya terdapat perbedaan yang signifikan setelah diberi video edukasi, dan pada kelompok kontrol didapatkan (1.000) artinya tidak terdapat perbedaan yang signifikan. Hasil Uji Mann-Whitney sebelum diberi video edukasi didapatkan (0.957) artinya tidak terdapat perbedaan yang signifikan antara kelompok perlakuan dan kontrol, sedangkan sesudah diberi video edukasi didapatkan (0.000) artinya terdapat perbedaan yang signifikan antara kelompok perlakuan dan kontrol. Pemberian edukasi dengan media video secara signifikan meningkatkan pengetahuan perawatan kaki pada pasien DM tipe 2.